2020
DOI: 10.1111/pim.12781
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐like particles expressing Plasmodium berghei MSP‐8 induce protection against P. berghei infection

Abstract: Aims: Merozoite surface protein 8 (MSP-8) of Plasmodium parasites plays an important role in erythrocyte invasion and is a potential malaria vaccine candidate. Methods and Results: In this study, virus-like particles (VLPs) expressing MSP-8 of Plasmodium berghei on the surface of influenza virus matrix protein 1 (M1) core protein were generated for vaccine efficacy assessment. Mice were intramuscularly (IM) immunized with MSP-8 VLPs twice and challenge-infected with P. berghei. We found that VLP vaccination el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…In the present study, both AMA1 and MIC were recognized by P. berghei antibody by western blot, which implies that both of these antigens were correctly expressed and reflect their native conformations [ 2 , 3 ]. VLPs immunization elicited P. berghei -specific IgG and IgG2a antibody responses, indicating VLPs containing both AMA1 and MIC were involved in protection.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the present study, both AMA1 and MIC were recognized by P. berghei antibody by western blot, which implies that both of these antigens were correctly expressed and reflect their native conformations [ 2 , 3 ]. VLPs immunization elicited P. berghei -specific IgG and IgG2a antibody responses, indicating VLPs containing both AMA1 and MIC were involved in protection.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous study, VLPs immunizations from Toxoplasma gondii antigenic proteins or P. berghei MSP-8 and MSP-9 significantly lessened inflammatory cytokine responses [ 2 , 5 , 28 ]. Consistent with these findings, in our current study, VLP-immunized mice showed significant reductions in pro-inflammatory cytokines IFN-γ and TNF-α compared to the naïve challenge control, which may contribute to lessened parasitemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, VLPs were shown to be equally effective inducers of cytotoxic T lymphocyte responses regardless of homologous or heterologous immunization methods [ 38 ], and this contributed to enhancing the CD8 + T cell circulation in the blood of mice. Although memory T cell responses were not assessed in the present study, our previous findings involving MSP-8 and MSP-9 VLP vaccines reported a potent induction of memory T cell responses following immunization [ 39 , 40 ]. This is also true for various vectored-vaccine platforms that utilized an immunization strategy similar to that incorporated in the present study [ 41 ].…”
Section: Discussionmentioning
confidence: 98%
“…Toxoplasma gondii RH, ME49, and P. berghei ANKA strains were maintained in seven-week-old female BALB/c mice obtained from NARA Biotech (Seoul, Korea) following the methods described previously [ 21 , 22 ]. Spodoptera frugiperda Sf9 insect cells were cultured in serum-free SF900-II medium (Invitrogen, Carlsbad, CA, USA) and subsequently used to generate recombinant baculovirus (rBV) and virus-like particles (VLPs).…”
Section: Methodsmentioning
confidence: 99%